Going chiral: overlap versus twisted mass fermions - Bietenholz, Wolfgang; Capitani, S.; Chiarappa, T.; Christian, N.; Hasenbusch, Martin; Jansen, K.; Nagai, K.-I.; Papinutto, M.; Scorzato, L.; Shcheredin, S.; Shindler, A.; Urbach, C.; et al. (Journal of high energy physics, 2004)
We compare the behavior of overlap fermions, which are chirally invariant, and of Wilson twisted mass fermions at full twist in the approach to the chiral limit. Our quenched simulations reveal that with both formulations of lattice fermions pion masses of 𝒪(250 MeV) can be reached in practical applications. Our comparison is done at a fixed value of the lattice spacing a ≃ 0.123 fm. A number of quantities are measured such as hadron masses, pseudoscalar decay constants and quark masses obtained from Ward identities. We also determine the axial vector renormalization constants in the case of overlap fermions.
Published 17 January 2005
Gesehen am 05.07.2022